Corporate Venture Management und Entrepreneurial Marketing - Thorsten Kliewe; Carina Alfert; Thomas Baaken (PraxisWISSEN Marketing, 2019)
Immer mehr Unternehmen gehen auf eine experimentelle Reise in die Zukunft - eine Zukunft, die vielfach von Ungewissheit geprägt ist. Corporate Venture Management befähigt etablierte Unternehmen, sich neben dem bestehenden Geschäft auf flexible und experimentelle Weise mit neuen Märkten und Geschäftsmodellen auseinanderzusetzen und so dem Innovator's Dilemma zu begegnen. Dabei wird etablierten Unternehmen ein zunehmendes Maß an Kreativität und das Hinterfragen bestehender Denkmuster abverlangt. Neben praxisgeleiteten Ansätzen in Form kurzer Fallstudien wird Effectuation als transformativer Ansatz im Entrepreneurial Marketing vorgestellt. – – More and more companies are undertaking an experimental journey into the future − a future that is often characterized by uncertainty. Corporate venture management enables established companies to deal with new markets and business models in a flexible and experimental way, in addition to their existing business, to respond to the innovator's dilemma. Established companies are required to be increasingly creative and to question existing decision-making patterns. In addition to practice-oriented approaches in the form of short case studies, Effectuation is presented as a transformative approach in Entrepreneurial Marketing.
Keywords: 650; Effectuation; Corporate Entrepreneurship; Corporate Venturing; Corporate Venture Management; Business Development; Strategisches Marketing; Entrepreneurial Marketing